2018
DOI: 10.5195/jmla.2018.196
|View full text |Cite
|
Sign up to set email alerts
|

Accessibility of published research to practicing veterinarians

Abstract: ObjectivesThis study established the percentage of veterinary research articles that are freely available online, availability differences inside and outside of core veterinary medicine publications, sources and trends in article availability over time, and author archiving policies of veterinary journals. This research is particularly important for unaffiliated practitioners who lack broad subscription access and the librarians who assist them.MethodsWeb of Science citation data were collected for articles pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The delay in the publication timeline observed may also be due to the increased volume of submissions originating from a breadth of veterinary conferences and the limited number of journals to which they were submitted. As open‐access journals gain popularity and standing in the veterinary community, journal options and opportunities to publish may increase, and we may start to see a decrease in the median time to publication 27 . There are, however, limited journals that are acceptable for residency certification, and this may also lead authors to submit to specific journals as we found the majority of VES abstract first authors were not yet board certified when they presented their research.…”
Section: Discussionmentioning
confidence: 93%
“…The delay in the publication timeline observed may also be due to the increased volume of submissions originating from a breadth of veterinary conferences and the limited number of journals to which they were submitted. As open‐access journals gain popularity and standing in the veterinary community, journal options and opportunities to publish may increase, and we may start to see a decrease in the median time to publication 27 . There are, however, limited journals that are acceptable for residency certification, and this may also lead authors to submit to specific journals as we found the majority of VES abstract first authors were not yet board certified when they presented their research.…”
Section: Discussionmentioning
confidence: 93%
“…The gap between access to the literature between individual and institutional level appears to be narrowing. A recent study suggested as much as 62% of the veterinary literature is available online freely via several avenues (Page, 2018). One is that authors upload their paper for others to read free of charge; this might be their submitted version, their accepted manuscript or the publisher's final version.…”
Section: Getting Full‐text Accessmentioning
confidence: 99%